Methodological Bases of Studying National Cuisine as a Phenomenon of Gastronomic Culture - Elena L. Iakovleva (Publishing house "Sreda", 2020)
The author outlines that in "current modernity" (Z. Bauman), among the urgent problems of research, one can name tradition, which is the foundation of culture. Many of its components are among those that are difficult to comprehend, and national cuisine is among them. Methods of research. In the presented article, national cuisine is examined through the prism of an analytical method that allows you to identify authentic ways of studying and showing its versatility. In the course of the research, a theoretical analysis of the methodological basis for the study of national cuisine as a phenomenon of gastronomic culture was carried out. It is noted that being a unique phenomenon of the traditional ethnic culture, national cuisine has its own gastronomic code and contains information about the specifics of the people's life, encrypted through processes related to food and its preparation. The author pays special attention to the fact that the most effective methods of researching national cuisine are structural, phenomenological and hermeneutic. They help to identify designs and highlight the structural components of national cuisine (culinary culture, culture of eating and gastronomic reflection), study and analyze them with the help of feelings and experience as a direct connection to each of them, comprehend the process of cooking based on the culinary recipe and the process of tasting, reveal the symbolic meanings of the elements of national cuisine and establish their origins. Results of research. The simultaneous use of phenomenological, structural and hermeneutic methods contributes to the comprehension of the gastronomic code of the people and the peculiarities of their cuisine. The knowledge gained allows us to interpret not only the secrets of national cuisine, but also the history and culture of the ethnos from new perspectives.